The effectiveness of workplace interventions for the prevention of alcohol use: A meta-analysis. - Fellbaum, Lena; Mojzisch, Andreas; Bielefeld, Laura; Benit, Nils; Soellner, Renate (Addiction, 2023)
Background and Aims: Previous research has pointed to the potential of workplace interventions addressing alcohol consumption. However, there is still no systematic overview of the effects of these interventions. Therefore, we aimed to quantify the effectiveness of workplace interventions addressing alcohol use by conducting a meta-analysis. Methods: A systematic literature search for randomized controlled trials of workplace alcohol interventions published between 1995 and 2020 was conducted in five databases. Studies were included if they were performed in the workplace and reported universal or selective interventions aiming for alcohol use reduction. Primary outcomes were any measures of alcohol use. Standardized mean effect sizes were used to calculate the meta-analytic random-effects-model. Additional analyses were carried out to identify potential moderators and to examine the amount of heterogeneity and publication bias. Results: Twenty studies with 4484 participants were integrated into the meta-analysis. Results revealed a significant overall mean effect indicating a reduction of alcohol use in favor of the treatment group (d = -0.16, 95% CI = [-0.2715; -0.0511]). Heterogeneity within the data structure was found to be moderate to substantial (I² = 75.9%, Q-test P < 0.001, Τ ² = 0.0375). Additional moderator analyses only showed a significant effect for length of measurement period (P = 0.049). Conclusions: Alcohol-related prevention programs conducted in the workplace have a statistically significant and favorable effect on alcohol consumption. Although the overall mean effect is considered to be small, it underlines the effectiveness of workplace interventions targeting a reduction in alcohol use.